Decision Support System for Feasibility of Marketing Chicken Using Weighted Product Method: Sistem Pendukung Keputusan Kelayakan Pemasaran Ayam Menggunakan Metode Weighted Product - eriwandi; Sarjon Defit; Sumijan (SYSTEMATICS, 2021)
Chicken is a farm animal that is loved by many people, where chicken contains many things that are needed by the body. To get the best chicken, the company needs to conduct a selection in determining the best chicken to be marketed to consumers. Selection Determining the best chicken to be marketed is part of the selection process. In the process of determining the best chicken PT. Japfa com feed Indonesia Tbk is carried out with a series of tests in the form of chicken size, feather color, weight, and body temperature. Therefore we need a decision support system with the weighted product (WP) method as an alternative solution of choice so that it runs effectively and reduces subjective assessments. From the test data, it can be concluded that the system is able to provide alternative choices effectively and reduce the element of subjectivity with a margin of error of 90% when compared to the same selection system.